Changes in the Composition of Heavy Crude Oil during the Simulation of Oil Displacement in Porous Media; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Chuikina D. I.; Savinykh Yu. V. Yurii Valentinovich; Stakhina L. D.; Kozlov V. V. (2018, 2018)
Title screen